Blood‐Inert Surfaces via Ion‐Pair Anchoring of Zwitterionic Copolymer Brushes in Human Whole Blood. (28th September 2012) - Chang, Yung; Shih, Yu‐Ju; Lai, Chia‐Jung; Kung, Hsiao‐Han; Jiang, Shaoyi
Abstract A strategy to create blood‐inert surfaces in human whole blood via ion‐pair anchoring of zwitterionic copolymer brushesand a systematic study of how well‐defined chain lengths and well‐controlled surface packing densities of zwitterionic polymers affect blood compatibility are reported. Well‐defined diblock copolymers, poly(11‐mercaptoundecyl sulfonic acid)‐block‐poly(sulfobetaine methacrylate) (PSA‐b‐PSBMA) with varying zwitterionic PSBMA or negatively charged PSA lengths, are synthesized via atom‐transfer radical polymerization (ATRP). PSA‐b‐PSBMA is grafted onto a surface covered with polycation brushes as a mimic polar/hydrophilic biomaterial surface via ion‐pair anchoring at a range of copolymer concentrations. Protein adsorption from single‐protein solutions, 100% blood serum, and 100% blood plasma onto the surfaces covered with PSA‐b‐PSBMA brushes is evaluated using a surface plasmon resonance sensor. Copolymer brushes containing a high amount of zwitterionic SBMA units are further challenged with human whole blood. Low protein‐fouling surfaces with >90% reduction with respect to uncoated surfaces are achieved with longer PSA blocks and higher concentrations of PSA‐b‐PSBMA copolymers using the ion‐pair anchoring approach. This work provides a platform to achieve the control of various surface parameters and a practical method to create blood‐inert surfaces in whole blood by grafting ionic‐zwitterionic copolymers to charged biomaterials via charge pairing.